PAVING BLOCK TANPA SEMEN BERBAHAN LIMBAH PLASTIK - Asnita Virlayani; Mustakim Mustakim; Asrul Asrul (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
The problem of plastic waste that is not handled and managed optimally can cause environmental damage. This study aims to test the compressive strength and water absorption value of paving blocks made of plastic which are designed using a mixed variation of V50-50 (50% sand, 50% plastic), V25-75 (25% sand, 75% plastic) and V0-100 (0% sand, 100% plastic) of the total proportion of the paving block mix. The method is carried out by melting PP (Polypropylene) mineral glass plastic, mixed with sand based on variations, printed according to the size of the paving block and used as a test sample in the form of a dice. The average compressive strength test results show that the sample with the code V25-75 has a relatively higher compressive strength value than V50-50 and V0-100. The average compressive strength value of the sample with code V25-75 is 11.53 MPa, followed by code V50-50 of 9.63 MPa, and the lowest is coded V0-100 of 3.70 MPa. The compressive strength value is influenced by the optimal percentage between sand and plastic, plastic serves as a binder for sand in a mixture of paving blocks. The percentage of water absorption value will continue to decrease along with the addition of plastic waste in the paving block mixture, V50-50 is 1.44, V25-75 is 0.88 and V0-100 is 0.16. This research is expected to be applied by the community to make paving block products, so that it can reduce the amount of plastic waste globally.